Multimedia Cloud Computing an Emerging Technology: Surve (International Journal of Engineering and Computer Science, 2017)
To provide rich media services, multimedia computing has emerged as a noteworthy technology to generate, edit, and search media contents, such as images, graphics, video, audio, and so on. For multimedia applications and services over the Internet and mobile wireless networks, there are strong demands for cloud computing because of the significant amount of computation required for serving millions of Internet or mobile users at the same time. This paper reviews brief literature on multimedia cloud computing aspects and describe some of the security issues in cloud computing, including data integrity, data confidentiality, access control, data manipulation in the encrypted data domain, with respect to the existing security algorithms.